Bone density and bone metabolic markers in active collegiate athletes: findings in long-distance runners, judoists, and swimmers - Matsumoto, T.; Nakagawa, S.; Nishida, S.; Hirota, R. (International Journal of Sports Medicine, 1997)
We investigated the bone metabolic system status of 103 male and female volunteer collegiate athletes, who were actively pursuing one of three different sports: Long-distance running (LR); judo (JU); and swimming (SW). The following parameters were evaluated: total body bone mineral density (TMBD); bone-forming metabolic markers; serum procollagen type I C-peptide (PICP) levels; bone alkaline phosphatase (B-ALP) content; bone resorption markers, urinary pyridinoline (Pyd) and deoxypyridinoline (Dpd) levels. We found that the TBMD and urinary Dpd values in JU athletes were significantly higher (p < 0.001) than in athletes of the same sex in the other two groups. The urinary Pyd level in male JU athletes was also higher (p < 0.001) than that in the other two groups, but that in females JU athletes was only higher (p < 0.01) than that in female LR athletes. The PICP levels were similar to the TBMD values in all groups. No differences in bone density or in bone metabolic markers were seen in LR and SW athletes of the same sex. We thus conclude that differences in bone mineral density are in part due to the demands of the specific sport, and that they are reflected in bone metabolic markers. In addition, the status of bone metabolic turnover in male JU athletes in training may be hypermetabolic and as well as that of female JU athletes with regular menses cycles.